Seroprevalence of Taenia saginata Cysts in Cattle, Human Hospital Cases, and Risk Factors for Human Taeniasis in Kajiado County, Kenya - Ruphline M. Anyango; Timothy M. Wachira; Gerald M. Muchemi (Veterinary Medicine International, 2023)
Taenia saginata is a zoonotic tapeworm that causes diseases in cattle and humans. A cross-sectional survey was conducted between June and July 2021 in Kajiado County, Kenya, to estimate the seroprevalence of Taenia saginata cysts in cattle presented for slaughter in Kitengela, Kiserian, and Keekonyokie slaughterhouses; determine the annual hospital reported cases of T. saginata in humans that visited all level 4 hospitals in Kajiado County between 2015 and 2021; and assess the risk factors for Taenia saginata in humans. Analyzed data in this study revealed that the seroprevalence of Taenia saginata cysts in cattle in the selected slaughterhouses was 2.67% (4/150). The meat inspectors recorded no cysts during the study period, confirming that antibody ELISA is three times as sensitive as meat inspection. Data from hospital records showed that a total of 1,487,687 patients visited different facilities in Kajiado County between 2015 and 2021. During the same period, 29 patients were diagnosed with human taeniasis. From the risk factors assessed, uninspected home slaughter (75%), consumption of raw/improperly cooked beef (100%), and open defecation by herders (11%) still pose a risk to humans getting infected by Taenia saginata, while the presence and use of latrines (89%) and availability, accessibility, and use of taenicides (89%) seem to have significantly contributed to the reduction of Taenia saginata prevalence in this region. It is recommended that control of the infection should be centered towards continuous focused education coupled with regular deworming of the herders and school going children. This will gradually result in behavior and culture change that will ultimately reduce the prevalence and lead to the elimination of the disease.